Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
0
Step-by-step explanation:
3ab + 5b - 6 when a = -1 and b is 3
→ First substitute a and b into 3ab
3 × -1 × 3 = -9
→ Substitute b into 5b
5 × 3 = 15
→ Connect all the terms together
-9 + 15 - 6
→ Simplify
0
Answer:
0
Step-by-step explanation:
3(-1)(3)+5(3)-6= -9+15-6=0
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.